2021
DOI: 10.1002/1873-3468.14168
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of the mouse LIM gene family reveals its roles in regulating pathological cardiac hypertrophy

Abstract: LIM‐domain proteins have been shown to be associated with heart development and diseases. Systematic studies of LIM family members at the genome‐wide level, which are crucial to further understand their functions in cardiac hypertrophy, are currently lacking. Here, 70 LIM genes were identified and characterised in mice. The expression patterns of LIM genes differ greatly during cardiac development and in the case of hypertrophy. Both Crip2 and Xirp2 are differentially expressed in cardiac hypertrophy and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In particular, XIRP2 shows differential expression during cardiac hypertrophy and HF. 85 Regarding the extracellular matrix, the levels of non-collagen proteins periostin and biglycan increase over time. Previous studies have shown that β-adrenergic receptor (β-AR) stimulation is the primary mechanism regulating cardiac output.…”
Section: Proteomics Of Hfmentioning
confidence: 99%
“…In particular, XIRP2 shows differential expression during cardiac hypertrophy and HF. 85 Regarding the extracellular matrix, the levels of non-collagen proteins periostin and biglycan increase over time. Previous studies have shown that β-adrenergic receptor (β-AR) stimulation is the primary mechanism regulating cardiac output.…”
Section: Proteomics Of Hfmentioning
confidence: 99%